ORGANIZING ACCOUNTING POLICIES IN TRADE ENTERPRISES - Ziyadullayevna, Bobomuradova Sarvinoz (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This article analyzes the issues of organizing accounting policies in trade enterprises based on the legislation of the Republic of Uzbekistan. Method: The article examines the legislative requirements for organizing accounting policies in trade enterprises, international experience, and practical problems encountered, and analyzes the results using tables and graphs. Results: The article examines the legislative requirements for organizing accounting policies in trade enterprises, international experience, and practical problems encountered, and analyzes the results using tables and graphs. Novelty: Accounting policy is an important document that regulates the financial accounting of a trading enterprise, and its proper organization ensures the financial stability of the enterprise and its operation in accordance with the law.